Analisis Tingkat Kepuasan dan Loyalitas Pengguna pada Prototype Aplikasi ITTS-Mart dengan Menggunakan Model E-Servqual - Yulianita, Ika; Zunaidi, Rizqa Amelia; Putra, Perdana Suteja (Program Studi Teknik Informatika Universitas Pamulang, 2024)
ITTS Mart is an e-commerce application developed by the Telkom Surabaya Institute of Technology (ITTS) as a platform that makes it easier for users to carry out buying and selling transactions for vegetables and fruit. This research examines the level of customer satisfaction with application use and the extent of customer loyalty so that customers can make repeat purchases continuously. The model used in this research is the E-Servqual model with three data processing, namely GAP Test, Customer Satifaction Index (CSI), Structural Equation Modeling (SEM), because these three data processing can be used to test the relationship between variables which can provide a deeper understanding. in-depth understanding of customer perceptions and expectations regarding ITTS Mart, as well as providing valuable recommendations to increase overall user satisfaction and loyalty. The research results showed that the Customer Satisfaction Index (CSI) test value on the ITTS-Mart application was 80.6%, meaning that application users were satisfied with the application service, the GAP test result was 1.13, which can be said to be good application quality, then the factors What influences the loyalty of ITTS-Mart application users is the Satisfaction variable with a P-Value of 0.000. So there still needs to be special attention in making improvements and evaluations related to the ITTS-Mart application so that it meets customer desires and needs.